Rancang Bangun Pengembangan Sistem Pompa Galon Air Otomatis Dengan Sensor Infrared Untuk Efisiensi Penggunaan Air Minum - Eka Nur Wahid; Dede Fauzul Iman; Repaldi Repaldi (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
This study examines the automation of electric gallon pumps for drinking water. This automation involves replacing the manual button on the gallon pump with a sensor, which turns on the pump and dispenses drinking water when the glass gets closer without pressing the button. This tool can also be used for gallons of drinking water ranging in size from 5 liters, 10 liters, to 15 liters. The system is designed for practical applications, and all its components are tested to understand their respective functions so as to understand the type of module that suits their needs. Test results reveal that the system is functioning as intended. Electric pump modules, infrared proximity sensors, and relay modules are some of its components.